Telaah Maqashid Al-Syari'ah antara Penalaran Tekstual dan Kontekstual (Studi Deskriptif Analisis) - Sahidin, Amir; Kamaluddin, Imam (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2023)
This article starts from misunderstanding of some Muslims in reasoning maqashid al-syari'ah. Some of them argue that maqashid al-syari'ah is only what appears of the text to nash, so they reason the nash textually. As a result, Islamic law becomes rigid and it is easy to blame you. Some of them reasoned too much about maqashid al-syari'ah, thus canceling the text of the nash. As a result, he was brave enough to deconstruct a permanent Islamic law. Therefore, this article will examine maqashid al-syari'ah with a fair and moderate study (wasathiyah) that is not as extreme as textual or contextual reasoning. Through a library research study with a descriptive analysis approach, it was found that wasathiyah reasoning in maqashid al-syari'ah reasoning is to distinguish between worship and muamalat matters in terms of the intentions behind them; seek maqashid al-shari'ah before determining the law; and has the principle that the shari'a which is built on the qath'i argument will not conflict with benefit and common sense.